Estimation of influence of exploration seismology works on sea fauna and flora - A. A. Mungiev (Юг России: экология, развитие)
On the basis of experimental researches of acoustic injuring influence on hydrobionts, dependence of hydrobiont`s destruction from distance up to a source of radiation is deduced. The received dependence can be used for an estimation of influence of exploration seismology works on sea fauna and flora and to be used by development of projects estimations of damages in sections «The Estimation of influence on an environment».